Evaluating abundance trends of iconic species using local ecological knowledge. (September 2018) - Peñaherrera-Palma, César; van Putten, Ingrid; Karpievitch, Yuliya V.; Frusher, Stewart; Llerena-Martillo, Yasmania; Hearn, Alex R.; Semmens, Jayson M.
Abstract: Abundance is commonly used to assess the status of wildlife populations and their responses to changes in management frameworks. Monitoring abundance trends often requires long-term data collection programs, which are not always carried out. One alternative to scientific surveys is to utilize the local ecological knowledge (LEK), from people in continuous interactions with the environment. We developed a semi-quantitative approach to assess shark population trends by using the LEK of non-extractive resource users. We carried out structured interviews with dive guides regarding the abundance trends of six shark species in the Galapagos Marine Reserve (GMR) across decades since the 1980s. Based on dive guides' LEK, we developed a virtual abundance change (VAC) model to assess the changes in abundance across decades. Our VAC analysis showed a 50% decline in hammerhead sharks and 30% decline in whitetip reef sharks. Silky sharks and Galapagos sharks were perceived to suffer an initial decline by 25% and 30% then stabilized. Whale shark abundance did not appear to have changed. Finally, blacktip sharks showed an apparent recovery after a decline by 25%. Furthermore, our VAC results were comparatively similar to empirical datasets from the GMR and neighboring protected areas of the Eastern Tropical Pacific. Our study highlights the value of LEK in assessing the state of marine resources in data-limited management regions. Our VAC method offers an alternative approach by which LEK can provide valuable insights into the historical trends of species abundance.